SIMULASI PROSES PENGECORAN DALAM TAHAPAN REVERSE ENGINEERING TOOLPOST MESIN BUBUT KONVENSIONAL - Dwiyanto, Agus; Hasanudin; Setiawan, Muhammad Diki; Kurniawan (KURVATEK, 2024)
Reverse engineering is an innovation in product development. Existing products are analyzed for further development or performance enhancement. This research focuses on the application of reverse engineering methods to create a toolpost, considering the need for toolpost spare parts for conventional lathes, which still relies on imports and is often unavailable in the market due to the discontinuation of manufacturers. The stages involved include gathering product information, analyzing functional features, measuring and modeling the toolpost, and conducting manufacturability analysis through casting simulation. This casting simulation aims to identify potential defects before the toolpost design is realized in a finished product. The simulation results indicate a total porosity defect of 2%, with defect locations identified in the gating system area and the hole area of the toolpost. Although defects are present, the percentage and locations of these defects are deemed unlikely to affect the functionality of the toolpost. The optimal pouring time is 2.38 seconds, and cooling time is 201.3 seconds to prevent cracking and deformation.